2011
DOI: 10.1371/journal.pone.0027869
|View full text |Cite
|
Sign up to set email alerts
|

hnRNP A1 and hnRNP F Modulate the Alternative Splicing of Exon 11 of the Insulin Receptor Gene

Abstract: Exon 11 of the insulin receptor gene (INSR) is alternatively spliced in a developmentally and tissue-specific manner. Linker scanning mutations in a 5′ GA-rich enhancer in intron 10 identified AGGGA sequences that are important for enhancer function. Using RNA-affinity purification and mass spectrometry, we identified hnRNP F and hnRNP A1 binding to these AGGGA sites and also to similar motifs at the 3′ end of the intron. The hnRNPs have opposite functional effects with hnRNP F promoting and hnRNP A1 inhibitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 36 publications
3
70
0
Order By: Relevance
“…We found a correlation between INSR splicing and expression of HNRNPA1 , SF3A1 and SFRS7 in the KOBS study (ESM Table 4). The strongest negative correlation was with HNRNPA1 , previously reported to inhibit exon 11 inclusion in HepG2 and HEK293 cells [6]. We acknowledge that other regulators of INSR splicing exist [6], and they may also be modified by weight loss.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…We found a correlation between INSR splicing and expression of HNRNPA1 , SF3A1 and SFRS7 in the KOBS study (ESM Table 4). The strongest negative correlation was with HNRNPA1 , previously reported to inhibit exon 11 inclusion in HepG2 and HEK293 cells [6]. We acknowledge that other regulators of INSR splicing exist [6], and they may also be modified by weight loss.…”
Section: Discussionmentioning
confidence: 67%
“…The strongest negative correlation was with HNRNPA1 , previously reported to inhibit exon 11 inclusion in HepG2 and HEK293 cells [6]. We acknowledge that other regulators of INSR splicing exist [6], and they may also be modified by weight loss. One limitation of this study is that INSR protein isoforms created by alternative splicing could not be detected because the difference between the protein isoforms is only 1 kDa (data not shown).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Interestingly, the splice regulators hnRNPF/H predicted to bind to the G-runs by the ESRsearch tool (http://esrsearch.tau. ac.il/) have been described to control alternative splicing in several cases [32][33][34]. Specifically, it has been shown that these proteins are able to enhance the usage of upstream splice donor sites [35] as observed for the G-runs in intron 3 of tpn.…”
Section: Discussionmentioning
confidence: 99%